Design and experiment on Silicon photonic sensor - Nurhidayah Abdul Rahman Tan (2015)
Design and experiment on the silicon photonic sensor is a conceptual understanding of how light travels through a medium which are guided by waveguides. The project gives information of what is going on inside a silicon photonic sensor when light travels through it by the simulated images of the sensor. Hence, it is crucial to accomplish and understand the key theory through this project. The purpose of this project is to understand the mode profiles of each mode number and how factors such as the mesh structure and size of a waveguide affect the light travelling through it. The modes are calculated using a software named MODE Solutions. The design is based on a rectangular/planar waveguide and also ring resonators. The material used for the rectangular waveguide is Silicon while the ring resonators used Silicon and Glass. The advancement of this project needs to be documented so as the next student who is doing this project as well as for a research relevant to silicon photonic sensor can used this documentation as a reference.